The semantic web - ISWC 2014 : 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I - Tudorache, Tania; Bernstein, Abraham; Welty, Chris; Knoblock, Craig; Vrandecic, Denny; Groth, Paul; Noy, Natasha; Janowicz, Krzysztof; Goble, Carole; Mika, Peter (Lecture Notes in Computer Science, 2014)
The two-volume set LNCS 8796 and 8797 constitutes the refereed proceedings of the 13th International Semantic Web Conference, ISWC 2014, held in Riva del Garda, in October 2014. The International Semantic Web Conference is the premier forum for Semantic Web research, where cutting edge scientific results and technological innovations are presented, where problems and solutions are discussed, and where the future of this vision is being developed. It brings together specialists in fields such as artificial intelligence, databases, social networks, distributed computing, Web engineering, information systems, human-computer interaction, natural language processing, and the social sciences. Part 1 (LNCS 8796) contains a total of 38 papers which were presented in the research track. They were carefully reviewed and selected from 180 submissions. Part 2 (LNCS 8797) contains 15 papers from the 'semantic Web in use' track which were accepted from 46 submissions. In addition, it presents 16 contributions of the RBDS track and 6 papers of the doctoral consortium.